Farmer’s Characteristic for Improvement Of “Chrysanthemum sp.” Farm Flower (Case Study at Kenteng Village, Bandungan Subdistrict) - Galatia, Erina Prima; Gayatri, Siwi; Prasetyo, Agus Subhan (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
Chrysanthemum farm has potential as a main source of income, especially when farmers start a profitable business by following the procedure of cultivation. This research aim was to analyze the effect of farmer characteristics including age, education, knowledge of the standard operating procedure of chrysanthemum cultivation, and farming experience to improve chrysanthemum farming. The research was held from February - March 2022 in Kenteng Village. The method of determining the sample was non-probability sampling or purposive sampling with 47 farmers as members of The Farmer Group. The data were collected by interview using a questionnaire and observation. The analytical method used descriptive analysis and multiple linear regression analysis. As a result, the average farmer’s age was 41 - 50 years old, 46,8% of the respondents had primary education, 55,3% of the respondents were in the moderate category of knowledge about chrysanthemum cultivation standard operational procedure, and 40,4% of the respondent’s experience were in The good category. 66,0% of the respondents were in the moderate category of the improvement cultivation of chrysanthemums. The result showed that the characteristics of farmers including age, education, knowledge, and experience had simultaneously influenced the improvement of chrysanthemum farms. There was an influence between age and knowledge toward improvement cultivation, however, there was no influence between education and farming experience for the improvement of chrysanthemum farms.